Trump : the art of the deal - Trump, Donald, 1946-; Schwartz, Tony, 1952- (Ballantine Books, 2015)
In 1987, Trump published an unguarded look at the mind of a brilliant entrepreneur and an unprecedented education in the practice of deal-making. Now republished, but not updated, the book still provides a guide to personal finance that also provides a look into Trump's life up to that point.